Public health strategies adopted to manage the increase of accesses to vaccination services, as a result of the application of the law 119/2017 : Vaccination services response to increase of accesses due to law 119/2017 - Costantino, Claudio; Casuccio, Alessandra; Sannasardo, Claudia Emilia; Vella, Carlotta; Scarpitta, Francesco; Randazzo, Maria Angela; Foresta, Angelo; Casuccio, Nicolò; Ventura, Gianmarco; Bono, Stefania Enza; Vitale, Francesco; Restivo, Vincenzo (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the work: In response to the alarming reduction of vaccination coverage rates, Italian Ministry of Health approved the law number 119/2017, which has extended the number of mandatory vaccinations, for school attendance, from four to ten. The present study aims to evaluate accesses to the vaccination services of the Palermo Local Health Unit (LHU) and the variation of the vaccination coverage rates for hexavalent and measles, mumps, rubella and varicella (MMRV) vaccines, after the implementation of the law 119/2017. Methods: An extent of opening hours and an involvement of other health-care professionals in the vaccination services of the Palermo LHU have been adopted to manage the excess of accesses after the introduction of 119/2017 law and to limit the discomfort of general population. Vaccination accesses and coverage rates were calculated from the electronic immunization registers. Results: An overall increase of about 15% of single vaccination accesses was observed in the three semester after the introduction of the law in the LHU of Palermo. A peak of 35,516 accesses was observed during the second semester of 2017 (+ 30% compared to the same semesters of 2016 and 2018). From 2016 to 2018, coverage rates for full hexavalent cycle and first dose of MMRV, at 24 and 36 months, and for full MMRV cycle and fourth dose of diphtheria, tetanus, pertussis, poliomyelitis (DTPa+IPV), among 6 years old children, showed considerable increases. Conclusions: Law 199/2017 demonstrated a high efficacy in increase vaccination coverage rates also in Sicily. The synergy established between the LHU and the University of Palermo allowed an excellent management of the accesses to vaccination services, making it possible to respond to the public health needs of the general population.